Assistance for pregnant women at risk in efforts to prevent pregnancy complications - Yoga Tri Wijayanti; Warlinda; Hartaty; Ririn Indriani; Fatimah (LPPM Politeknik Sandi Karsa, 2025)
High-risk pregnancy is a condition that can increase maternal and fetal morbidity and mortality, so it requires special attention and treatment. This community service aims to assist pregnant women who are classified as high risk to prevent complications during pregnancy and childbirth. Implementing the activity includes health counseling, routine health check-ups, nutritional counseling, and early detection training on pregnancy danger signs. The service team involves medical personnel, midwives, and nursing students as facilitators and field assistants. The results showed an increase in participants' knowledge of pregnancy hazards (from 42% to 87%), an increase in adherence to regular antenatal visits (from 60% to 95%), and a change in healthy living behaviors in most participants. In addition, this program has succeeded in strengthening the relationship between the community and health workers and strengthening the family's role in supporting healthy pregnancies. In conclusion, this mentoring activity is effective in increasing awareness, knowledge, and readiness of pregnant women at risk in dealing with pregnancy and childbirth. Sustainability of the program and support from relevant parties are needed to reach more targets and strengthen the referral system for high-risk pregnant women at the primary level